Influence of Relative Position of Gears and Casing Wall Shape of Gear Box on Churning Loss under Splash Lubrication Condition—Some New Ideas. Issue 6 (1st November 2016) - Chen, Sheng-Wei; Matsumoto, Susumu
ABSTRACT: A new rotatable test rig is developed to perform oil churning loss experiments to clarify the influence of the relative position of gears and casing wall shape of gear box under splash lubrication condition. Torque losses are measured and photos are taken using a stroboscope to observe the oil behavior. Based on the test results, it has been confirmed that in addition to the well-known factors, relative position and casing wall shape have significant effects on the churning loss and should be considered in the modeling process, which has been neglected in most previous studies. In this article, the importance of the steady-state oil surface profile (SOSP) is emphasized. New ideas are proposed on how other working conditions such as immersion depth and rotation speed influence the churning loss.